Cases of high mortality in cull sows and feeder pigs associated with Streptococcus equi subsp. zooepidemicus septicemia. (July 2020) - Sitthicharoenchai, Panchan; Derscheid, Rachel; Schwartz, Kent; Macedo, Nubia; Sahin, Orhan; Chen, Xuhua; Li, Ganwu; Main, Rodger; Burrough, Eric
Investigations of 2 cases of high mortality in cull sows and feeder pigs from a buying station in Ohio and cull sows at an abattoir in Tennessee were conducted at the Iowa State University Veterinary Diagnostic Laboratory. The animals were presented as weak, lethargic, and some with high fever. Rapidly escalating mortality was reported to be as high as 30–50% within groups at the buying station over 8–10 d, and 30–40% over 5–7 d at the abattoir. Splenomegaly and red lymph nodes were the most consistent macroscopic findings, with scant fibrinous polyserositis observed in one sow. The microscopic lesions of vasculitis, fibrin thrombi, fibrinosuppurative polyserositis, and intralesional bacteria were consistent with acute bacterial septicemia. Bacterial culture isolated Streptococcus equi subsp. zooepidemicus ( S. zooepidemicus ) from multiple organs, including spleen, lung, and kidney. PCR tests were negative for African swine fever virus, classical swine fever virus, Erysipelothrix rhusiopathiae, porcine reproductive and respiratory syndrome virus, porcine circovirus 2, and Salmonella spp. Porcine circovirus 3 was inconsistently detected at low levels by PCR, with a lack of associated lesions. Next-generation sequencing identified S. zooepidemicus and porcine partetravirus in the serum sample of the feeder pig from the buying station. Phylogenetic analysis of the szP gene indicated that the S. zooepidemicus isolates from Ohio and Tennessee are in genotype VI. We conclude that the cause of these high mortality events in swine was S. zooepidemicus septicemia.